2017
DOI: 10.1289/ehp478
|View full text |Cite|
|
Sign up to set email alerts
|

Prenatal PBDE and PCB Exposures and Reading, Cognition, and Externalizing Behavior in Children

Abstract: Background:Prenatal polybrominated diphenyl ethers (PBDEs) and polychlorinated biphenyls (PCBs) exposures may influence children’s neurodevelopment.Objective:We examined the association of prenatal PBDE and PCB exposures with children’s reading skills at ages 5 and 8 years, Full-Scale Intelligence Quotient (FSIQ), and externalizing behavior problems at age 8 years.Methods:From 239 mother–child pairs recruited (2003–2006) in Cincinnati, Ohio, we measured maternal serum PBDE and PCB concentrations, assessed chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 49 publications
2
49
2
1
Order By: Relevance
“…Even though the concentrations of the five different congeners were highly correlated in the current study (r's ranging between .74 and .99), previous studies have shown that different congeners are associated with different cognitive functions (Herbstman et al, 2010;Zhang et al, 2017). However, the contribution (i.e., weight) of each congener differed by outcome.…”
Section: Prenatal Pbde Serum Concentrations Are Associated With Globacontrasting
confidence: 77%
See 1 more Smart Citation
“…Even though the concentrations of the five different congeners were highly correlated in the current study (r's ranging between .74 and .99), previous studies have shown that different congeners are associated with different cognitive functions (Herbstman et al, 2010;Zhang et al, 2017). However, the contribution (i.e., weight) of each congener differed by outcome.…”
Section: Prenatal Pbde Serum Concentrations Are Associated With Globacontrasting
confidence: 77%
“…Congener 100 strongly contributed to the global efficiency of visual brain areas (i.e., inferior occipital gyrus and lingual gyrus), while congeners 28 and 153 particularly contributed to global efficiency of sensorimotor areas (i.e., precentral gyrus and superior temporal gyrus). Even though the concentrations of the five different congeners were highly correlated in the current study (r's ranging between .74 and .99), previous studies have shown that different congeners are associated with different cognitive functions (Herbstman et al, 2010;Zhang et al, 2017). It may be hypothesized that different congeners affect the function of different thyroid hormones (Herbstman et al, 2010;Zhang et al, 2017), and receptors for these hormones are expressed in distinct brain regions (Constantinou, Margarity, & Valcana, 2005).…”
Section: Prenatal Pbde Serum Concentrations Are Associated With Globacontrasting
confidence: 60%
“…To assess adaptive and behavioral problems in children, parents were requested to complete the Behavioral Assessment System for Children-2 (BASC-2) (Reynolds and Kamphaus, 2004). We focused on FSIQ and Externalizing Problems and its subscales (hyperactivity, aggression, conduct disorder), because prenatal PBDEs were significantly associated with FSIQ deficits and increased externalizing behavior in several epidemiologic studies (Chen et al, 2014; Cowell et al, 2015; Eskenazi et al, 2013; Roze et al, 2009; Zhang et al, 2016). The BASC-2 has a population mean of 50±10, with higher scores indicating increased problem behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from several epidemiological studies indicates that PBDEs are neurotoxic when exposure occurs during fetal development, with reports of decrements in Full Scale IQ (FSIQ), impaired executive function, lower reading and language abilities, and increased attention deficit/hyperactivity disorder (ADHD) related behaviors (Chen et al, 2014; Cowell et al, 2015; Ding et al, 2015; Eskenazi et al, 2013; Herbstman et al, 2010; Shy et al, 2011; Vuong et al, 2016; Zhang et al, 2016). Postulated mechanisms by which PBDEs may exert neurotoxic effects include indirectly affecting brain development through thyroid hormone disruption or directly acting on brain cells by causing oxidative stress, interfering with signal transduction, altering cholinergic system responses, inducing neuronal apoptosis, and altering neurotransmitter release and function (Costa et al, 2014; Costa and Giordano, 2011; Dingemans et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…PBDE exposure during fetal brain development is associated with deficits in cognitive function and behavior, including lower scores for full scale IQ (FSIQ), language, memory, reading, and executive function, as well as increased hyperactivity and attention problems (Chen et al, 2014; Cowell et al, 2015; Ding et al, 2015; Eskenazi et al, 2013; Gascon et al, 2011; Herbstman et al, 2010; Roze et al, 2009; Sagiv et al, 2015; Shy et al, 2011; Vuong et al, 2016; Zhang et al, 2017). In addition, postnatal exposure to PBDEs has also been associated with poorer FSIQ, slower processing speeds, inattention, and poorer social skills, lending evidence to support that PBDE neurotoxicity also occurs during childhood, when the brain is continuing to undergo synapse pruning and myelination (Adgent et al, 2014; Eskenazi et al, 2013; Gascon et al, 2011; Hoffman et al, 2012; Sagiv et al, 2015).…”
Section: Introductionmentioning
confidence: 99%